2015
DOI: 10.1371/journal.pone.0138552
|View full text |Cite
|
Sign up to set email alerts
|

Occult HBV Infection May Be Transmitted through Close Contact and Manifest as an Overt Infection

Abstract: The importance of transmission of occult HBV infection (OBI) via transfusion, organ transplantation and hemodialysis has been widely recognized. However, data regarding the transmission of OBI through close contact remain limited. In this study, serum samples were obtained from a child and his parents. The child had received the standard vaccination regimen at birth and produced protective antibody. Sera were tested for HBV serological markers. Nested PCR assays were used to detect HBV DNA and the amplicons we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…Some studies have suggested that the anamnestic immune response may play role in protection against HBV infection, although the titer of antibody has decreased below 10 mLU/mL . However, more and more studies have shown that chronic HBV carriage, detected by the presence of HBsAg in the blood, develops in some vaccines, especially in endemic regions . Whether booster doses of vaccine are necessary to maintain long‐term immunity has become an important issue.…”
Section: Disscusionmentioning
confidence: 99%
“…Some studies have suggested that the anamnestic immune response may play role in protection against HBV infection, although the titer of antibody has decreased below 10 mLU/mL . However, more and more studies have shown that chronic HBV carriage, detected by the presence of HBsAg in the blood, develops in some vaccines, especially in endemic regions . Whether booster doses of vaccine are necessary to maintain long‐term immunity has become an important issue.…”
Section: Disscusionmentioning
confidence: 99%
“…The risk of developing OBI is higher in certain populations, including HIV-positive individuals [8]. Multiple studies have investigated OBI in this high-risk cohort and reported variable prevalence rates between 0%-89.5% [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Hu ve ark. yaptıkları çalışmada anne ya da babasında okült hepatiti olan çocuklarda enfeksiyon olabileceğini ve okült hepatititin kapalı temasla da bulaşabileceğini göstermişler [6] [15]. Bizim çalışmamızda hastaların HBsAg negatif idi ve HBV-DNA saptanan 10 plasma örneğinin 7 (%70)'sinde HBV-DNA düzeyi < 6IU/ml iken 3 (%30)'ünde HBV-DNA düzeyi > 6IU/ml olarak bulundu.…”
Section: Discussionunclassified